Diversity and Abundance of Hymenopterous Parasitoids Associated with Anastrepha fraterculus (Diptera: Tephritidae) in Native and Exotic Host Plants in Misiones, Northeastern Argentina - Schliserman, Pablo (2010)
Some Major host species used by the tephritid fruit flies Anastrepha fraterculus (Wiede-mann) and Ceratitis capitata (Wiedemann), including Acca sellowiana (O. Berg) Burret, Campomanesia xanthocarpa O. Berg, Psidium guajava L., Prunus persica (L.) Batsch, Eriobotrya japonica (Thunb.) Lindl., Citrus reticulata Blanco var. Murcott, C. aurantium L., C. paradisi Macfadyen var. Dalan Dan, and C. paradisi var. Sudashi, were sampled for fruit fly larvae between Feb and Dec 2000 in the northernmost section of the Paranaense forest, in the Province of Misiones, NE Argentina. Both A. fraterculus and C. capitata were obtained from these host plant species, with A. fraterculus accounting for 93% of all tephritid puparia identified. Ten species of larval-pupal parasitoids were recovered from A. fraterculus; Doryctobracon areolatus (Szépligeti), D. brasiliensis (Szépligeti), Utetes anastrephae (Viereck), Opius bellus (Gahan), Diachasmimorpha longicaudata (Ashmead) (Opiinae, raconidae), Odontosema anastrephae Borgmeier, Lopheucoila anastrephae (Rohwer), Aganaspis pelleranoi (Brèthes) (Eucoilinae, Figitidae), Asobara anastrephae (Muessebeck) (Alyssinae, Braconidae), and Aceratoneuromyia indica (Silvestri) (Tetrastichinae, Eulophidae). All these parasitoids, with the exception of D. longicaudata and A. indica, are native to the Neotropical region. No parasitoids were recovered from C. capitata puparia. Asobara anastrephae and O. anastrephae are newly recorded in Argentina, whereas D. brasiliensis, U. anastrephae, and L. anastrephae are newly reported in Misiones. The eucoiline A. pelleranoi wasthe most abundant parasitoid species. Acca sellowiana and P. guajava harbored the highest parasitoid abundance and diversity.